1H NMR-Based Metabolic Profiling of Urine from Mice Fed Lentinula edodes-Derived Polysaccharides - Xu Xiaofei; Yang Jiguo; Ning Zhengxiang; Zhang Xuewu (Polish Journal of Food and Nutrition Sciences)
A heteropolysaccharide, named L2, from Lentinula edodes has been proved to possess immunostimulating and anti-ageing activities in previous studies, but its acting mechanism was not completely understood. In this study, 1H NMR spectroscopy approach was employed to investigate the metabolic profiles of the urine from adult mice after L2 intervention. Using principal component analysis (PCA) and partial least squares-discriminate analysis (PLS-DA), 22 potential biomarkers were found to be mainly involved in some metabolic pathways: amino acid metabolism, energy metabolism, lipid metabolism, tricarboxylic acid (TCA) cycle, urea cycle and gut microbiota metabolism. Among them, the significantly altered metabolites include: elevated glutamate (75%) and creatine (64%); decreased proline (65%), betaine (58%), fucose (63%) and dimethylamine (59%). In conclusion, the present data is helpful to understand the mechanisms related to previously confirmed immunomodulation and anti-aging effects of L2, and provide valuable information for mining new functions of L2.